Evaluation of nutritional intake and dietary habits in football referees - Gonçalves, Liliana (2006)
Soccer is a very demanding activity, not only to soccer playersbut also to referees, who have to occupy the better field position inorder to have a correct judgment of the match. Although there arevarious studies about nutritional evaluation in soccer players,scientific literature neglects the referee role as an athlete, which isverified in lack of studies in this population. In our study, referees(n=23) completed a 7-day dietary record and the results showed thatthere were no differences between main and assistant referees.Energetic intake was 2813 ± 287 kcal/day with a contribution of18.5%, 44.5% and 34.4% from protein, carbohydrate and fat,respectively. Carbohydrate (4.1 . g kg1 . day1), fiber and waterintakes were low. Dietary assessment showed excessive sugar (18.6%energy), cholesterol (449 mg) and sodium (2790 mg) intakes.Participants had a probably inadequate intake of vitamin E (40%RDA) and folate (71.5% RDA) and a possibly inadequate intake ofvitamin A (76.8% RDA), calcium (96.5% AI), potassium (79.7% AI)and magnesium (94.3% RDA). On average, athletes reported eatingon ~5 separate occasions each day. Breakfast, lunch and dinner werethe main contributors to the energetic intake (14.1%, 31.1% and35.0%, respectively). The out meals (lunch and dinner) had a higherenergy, fat, saturated fat and water intakes and lower intake ofsugars and polyunsaturated fats. This population showed moreconcern in competition than in training days, especially, inpreparation and recuperation periods. Dietary education couldimprove referees performance but also promote healthy dietarypractices.